2017
DOI: 10.1371/journal.pone.0173239
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum lactate with outcome after out-of-hospital cardiac arrest treated with therapeutic hypothermia

Abstract: AimsLactate reflects hypoxic insult in many conditions and is considered as a prognosis factor. But, after cardiac arrest, its interest is still debated. Our study aimed to assess the prognosis value of lactate in out-of-hospital cardiac arrest patients treated with therapeutic hypothermia.MethodsThis retrospective observational study included out-of-hospital cardiac arrest patients treated with therapeutic hypothermia in four ICUs. Lactate levels were compared at different times during the first 24 hours acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
2
13
0
2
Order By: Relevance
“…Consistent with this, admission lactate would be a surrogate marker of the severity of pre‐ and intra‐arrest ischemia. Our findings that elevated admission lactate was associated with increased mortality are in line with several previous studies . Contrary to our findings, however, studies by Starodub and Donnino found no significant association between mortality and admission lactate, which might be attributed to multiple factors, such as sample size, target population and different endpoints.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with this, admission lactate would be a surrogate marker of the severity of pre‐ and intra‐arrest ischemia. Our findings that elevated admission lactate was associated with increased mortality are in line with several previous studies . Contrary to our findings, however, studies by Starodub and Donnino found no significant association between mortality and admission lactate, which might be attributed to multiple factors, such as sample size, target population and different endpoints.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, normalization of lactate has proved to be clinically useful and is currently recommended as an endpoint in resuscitation of sepsis patients, albeit the level of evidence is low. In the context of OHCA patients, admission lactate and lactate clearance seem to be weakly related to outcome but results are conflicting . The aggregated evidence is thus at a low level and mainly based on small, retrospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac arrest patients, it may be affected by low cardiac output by chest compression during resuscitation [24]. Some observational studies have reported that metabolic acidosis after ROSC is correlated with the duration from arrest to ROSC and is associated with neurological outcome among OHCA patients [8,[25][26][27][28]. Respiratory acidosis, the other cause of severe acidemia, indicates inadequate discharge of carbon dioxide and is mostly caused by low venous return by chest compression and insufficient alveolar ventilation during resuscitation [24,29].…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Several observational studies have shown that serum lactate concentration in OHCA patients was influenced by factors in addition to the duration of cardiac arrest, including vasopressors, high arterial oxygen partial pressure, and decreased renal function [14, 45]. Serum lactate seems to be a comprehensive marker of severity in OHCA patients [46], and the association of serum lactate concentrations and neurological outcome has been described in many previous studies [1417, 47, 48]. In this study, both crude and predicted probability of 30-day favorable neurological outcomes decreased with increasing serum lactate concentration after ROSC (Fig.…”
Section: Discussionmentioning
confidence: 99%